Chronic and recurrent appendicitis: review article and cases report - Rocha, José Joaquim Ribeiro; Aprilli, Francisco; Féres, Omar (Medicina (Ribeirao Preto), 2001)
Chronic and recurrent appendicitis are pathologic conditions that differ from acute appendicitis, the most common affection of the vermiform appendix. The objective of the present study was to describe in detail the clinical features, diagnosis and pathology of those conditions.